PRODUK KOLEKBINDO (KOMIK LEKSIKON BAHASA INDONESIA) SEBAGAI MEDIA SOSIALISASI KONSEP KATA DALAM BAHASA INDONESIA - Anisa Setiani; Hermawati .; Mufidah Nur Azizah (Risenologi, 2019)
Indonesian language society still has minimal knowledge and lowly comprehension about the concept of words in Indonesian language. This phenomenon raises conflicts, one of them is misconceptions between speakers. Solution that can be done is the socialization of concept of Indonesian words. Based on that solution, this research produces new product to socialize the concept of Indonesian words called Kolekbindo (Komik Leksikon Bahasa Indonesia), namely the socialization media of concept of Indonesian words-based comic strips digital spreaded through social media. The method which is used on this research is R&D method (Research and Development). The purpose of this research is to produce new socialization media of Indonesian words. The results of this research can be described as: (1) Kolekbindo has an attractive style of paint and colour combination; (2) The layout is neat; (3) The type and size of the font is clear and the contents are easy to understand; (4) Contrasting characters and unique names is so interesting; and (5) Kolekbindo beneficial of being a media to socialize the Indonesian word’s concepts. Based on the results of the questionnaire, Kolekbindo's usefulness as a socialization media of Indonesian words has a percentage of 85.80% with very good criteria.